Effect Of Brushing Small White Ginger Extract Paste On Mechanical Strength Of Heat-Cured Acrylic Resin Plates - Debby Saputera; Beta Widya Oktiani; R. Harry Dharmawan Setyawardhana; I Wayan Arya Krishnawan Firdaus; Ririn Handayani; Ade Nia Karlina; Nor Najwa (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Brushing dentures with conventional toothpaste may compromise the mechanical and physical properties of heat-cured acrylic resin because of its high abrasive content. Small white ginger extract paste, which contains phenolic compounds, presents potential as an alternative cleansing agent. The present study analyzes the effect of brushing with small white ginger extract paste on the surface hardness, impact strength, and flexural strength of heat-cured acrylic resin plates. Materials and Methods: This study used heat-cured acrylic resin specimens (65 x 10 x 2,5 mm) and divided them into three brushing groups: small white ginger extract paste, placebo paste, and distilled water. These groups were evaluated to test surface hardness (12 specimens), impact strength (27 specimens), and flexural strength (24 specimens). Data were analyzed using the One-Way ANOVA test. Results and Discussion: The mean decrease in hardness for the ginger, placebo, and distilled water groups was 1 VHN, 0.6 VHN, and 1.2 VHN, respectively, indicating no significant difference between the ginger and control groups (p > 0.05). The mean impact strength values for the ginger, placebo, and control groups were 55×103 J/mm², 50×103 J/mm², and 42×103 J/mm², respectively, demonstrating a significant difference(p<0,05). The mean flexural strength values were 96.96 MPa (ginger), 97.97 MPa (placebo), and 96.22 MPa (control), with the One-Way ANOVA test showing no significant difference (p>0,05). Conclusion: Brushing with small white ginger extract paste significantly increases impact strength without significantly reducing surface hardness or flexural strength compared to control groups.